In vitro and in vivo biocompatibility of alginate dialdehyde/gelatin hydrogels with and without nanoscaled bioactive glass for bone tissue engineering applications - Rottensteiner, Ulrike; Sarker, Bapi; Heusinger, Dominik; Dafinova, Diana; Rath, Subha N.; Beier, Justus; Kneser, Ulrich; Horch, Raymund E.; Detsch, Rainer; Boccaccini, Aldo R.; Arkudas, Andreas (Materials, 2014)
In addition to good mechanical properties needed for three-dimensional tissue engineering, the combination of alginate dialdehyde, gelatin and nano-scaled bioactive glass (45S5) is supposed to combine excellent cellular adhesion, proliferation and differentiation properties, good biocompatibility and predictable degradation rates. The goal of this study was to evaluate the in vitro and in vivo biocompatibility as a first step on the way to its use as a scaffold in bone tissue engineering. In vitro evaluation showed good cell adherence and proliferation of bone marrow derived mesenchymal stem cells seeded on covalently crosslinked alginate dialdehyde-gelatin (ADA-GEL) hydrogel films with and without 0.1% nano-Bioglass® (nBG). Lactate dehydrogenase (LDH)- and mitochondrial activity significantly increased in both ADA-GEL and ADA-GEL-nBG groups compared to alginate. However, addition of 0.1% nBG seemed to have slight cytotoxic effect compared to ADA-GEL. In vivo implantation did not produce a significant inflammatory reaction, and ongoing degradation could be seen after four weeks. Ongoing vascularization was detected after four weeks. The good biocompatibility encourages future studies using ADA-GEL and nBG for bone tissue engineering application. © 2014 by the authors.
Keywords: Alginate dialdehyde; Biocompatibility; Gelatin; Mesenchymal stem cells; Nano-Bioglass®; Tissue engineering